Abundance, Attack Intensity, and Distribution of Spodoptera frugiperda J.E. Smith in Kulon Progo, Yogyakarta - Putra, Ichsan Luqmana Indra; Saputra, Wahyu Hana; Hanafi, Yahya (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2024)
Spodoptera frugiperda is an invasive corn pest from America and has entered Indonesia, including Kulon Progo. However, the abundance, attack intensity, and distribution of S. frugiperda have never been reported from Kulon Progo. This study aimed to analyze the abundance, attack intensity, and distribution of S. frugiperda larvae in Kulon Progo. This research was conducted from January to March 2023. Sampling locations were determined using the purposive sampling method. The egg packages and larvae of S. frugiperda found were counted to determine the abundance of S. frugiperda. The intensity of S. frugiperda infestation was calculated using the letter W scouting method. The results showed that 24 S. frugiperda egg packages were obtained in Kulon Progo, and the abundance of S. frugiperda was 0.01 individuals per plant. The attack intensity of S. frugiperda in Kulon Progo reached 4.97%, with the highest attack intensity in Nanggulan (8%) and the lowest in Wates (1.5%). The larvae of S. frugiperda are distributed in four sub-districts in Kulon Progo. This study concluded that the attack intensity of S. frugiperda in Kulon Progo was included in the mild category.